Estabelecimento das características cognitivas, fisiológicas e psicológicas no desempenho dos trabalhadores através de modelos representativos: o caso de uma indústria de calçados da Paraíba. - Almeida, Matheus das Neves (2013)
There is strong evidence that a relationship exists between human factors and human performance in production systems where the workforce is predominant. On the other hand, researches regarding this relationship are scarce in the recent literature. Moreover, these researches conducted only consider the performance from the perspective of quality and / or human error, that are just two of its many facets in the literature. However, this study considered the performance under a different perspective, to the investigate it as the number of pieces produced. Treat performance from the perspective of production quantity is important because this is a measure widely used to measure performance in assembly lines. In consequence of the established context, the objective of this research was to identify the cognitive, physiological and psychological characteristics that influence the performance of workers in terms of quantity of pieces produced in activity collage tennis on an assembly line. In this sense, was selected a set of cognitive, physiological and psychological characteristics a taxonomy called PIF's (Performance Influencing Factors), in which these three characteristics are used together to measure the performance of workers. Subsequently, was verified the interrelationship between the selected set and performance. The experiment was conducted in a shoes company in the State of Paraíba that has several assembly lines of shoes and evaluates the performance of its employees by the number of pieces per hour. As a result, was generated generalized linear models (GLM). Among the models that best explained this relationship was a MLG (the response variable) has an inverse normal distribution. This model has a pseudo-R2 equal to 0.81. Moreover, the human characteristics were considered significant: experience, age, gender, training, skill and pain.